Management of Insomnia in Hemodialysis Patients: A Literature Review - Nisrina Nur Aini; Arina Maliya (Jurnal Berita Ilmu Keperawatan, 2020)
Introduction: Hemodialysis (HD) therapy is the most common therapy for patients with End Stage Renal Disease (ESRD). Insomnia prevalent among dialysis patients which affects their quality of life and death. Although hemodialysis therapy has been proven to prolong survival, the action of hemodialysis therapy has complications that cause symptoms, one of which is sleep disturbance. Complaints of sleep disorders that are often encountered in dialysis units are experienced by 50-80% of dialysis patients. Of the various sleep disorders, insomnia is one of the symptoms that is often experienced by ESRD patients. Methods: A literature review comparing several literatures through the search of accredited journal sites such as PubMed, Elsevier, ResearchGate, and Neliti with the keywords management insomnia in hemodialysis patients in the 2015-2020 period. Research Results: Management of insomnia is reviewed with the aim of providing guidance to encourage treatment. In the six journals reviewed, education on sleep hygiene, CBT-I, relaxation therapy, massage therapy, and drug administration (with caution) improving the quality of sleep for hemodialysis patients. Conclusions: Pharmacological and non-pharmacological management to overcome insomnia in hemodialysis patients can be given by considering the factors that influence it. Management is advised to use a nonpharmacological approach first. The administration of pharmacological therapy is recommended only for short-term use, used with caution in hemodialysis patients.